A new subgenus and new species of Orthocladius van der Wulp, with a phylogenetic evaluation of the validity of the subgenera of the genus (Diptera: Chironomidae) - Sæther, Ole A. (Zootaxa, 2005)
A new subgenus, Mesorthocladius, of the genus Orthocladius v. d. Wulp is erected and diagnoses are provided for all stages and both sexes. Orthocladius (Mesorthocladius) lamellatus sp. n. and O. (Mesorthocladius) nimidens sp. n. are described in both sexes and all stages. Orthocladius (Euorthocladius) annellae sp. n. is described in both sexes and the pupa. The females of O. (Euorthocladius) rivicola Kieffer, O. (Eurthocladius) ashei Soponis, and O. (Orthocladius) dentifer Brundin are described for the first time. The larva of O. (Orthocladius) nitidoscutellatus Lundström (syn. Orthocladius trigonolabis Edwards) is described for the first time. A parsimony analysis of all species of Orthocladius with known pupae and male imagines is performed. The subgenera Eudactylocladius Thienemann and Euorthocladius Thienemann are always monophyletic, while Symposiocladius Cranston is paraphyletic before successive reweighting, but monophyletic after; Mesorthocladius is monophyletic before reweighting, but paraphyletic after; and Orthocladius s. str. is polyphyletic before reweighting and monophyletic after. Keys to subgenera for both sexes and all stages are given.